2013
DOI: 10.3892/ijo.2013.1893
|View full text |Cite
|
Sign up to set email alerts
|

Altered cardiac muscle mTOR regulation during the progression of cancer cachexia in the ApcMin/+ mouse

Abstract: Cancer cachexia is a muscle wasting condition that occurs in response to a malignant growth in the body. The mechanisms regulating cardiac muscle mass with cachexia are not well understood. Using the ApcMin/+ mouse model of colorectal cancer, we investigated how cachexia affects the regulation of 5′-adenosine monophosphate-activated protein kinase (AMPK), protein kinase B (Akt) and mammalian target of rapamycin (mTOR) signaling in the heart. Compared to age-matched C57BL/6 (BL6) mice, ApcMin/+ body mass and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
49
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 30 publications
(37 reference statements)
5
49
1
1
Order By: Relevance
“…Consistent with the increased AMPK phosphorylation, markers of autophagy including LC3-II, cathepsin L, and beclin were elevated in cachectic hearts from tumorbearing rodents, and electron microscopy has revealed the presence of double-membraned autophagic vacuoles containing portions of cytoplasm, mitochondria, and myelin-like structures (25,67,101).…”
Section: Pathogenesis Of Cardiac Atrophy In Cancer Cachexia: Protein mentioning
confidence: 66%
See 3 more Smart Citations
“…Consistent with the increased AMPK phosphorylation, markers of autophagy including LC3-II, cathepsin L, and beclin were elevated in cachectic hearts from tumorbearing rodents, and electron microscopy has revealed the presence of double-membraned autophagic vacuoles containing portions of cytoplasm, mitochondria, and myelin-like structures (25,67,101).…”
Section: Pathogenesis Of Cardiac Atrophy In Cancer Cachexia: Protein mentioning
confidence: 66%
“…Interestingly, the reductions in mTOR/S6/4E-BP1 in this study occurred in the face of elevated Akt (protein kinase B) phosphorylation (67), but studies have found that IL-6-mediated suppression of this pathway is independent of Akt (90). Cachectic hearts from Apc Min/ϩ mice also exhibited increased phosphorylation of 5=-adenosine monophosphate-activated protein kinase (AMPK), which can lead to autophagy and inhibition of mTOR, and is suggestive of increased signaling of degradative pathways (67). However, phosphorylation of Bad (Ser136), which reduces Bad-mediated apoptosis and cell death was increased in Apc Min/ϩ hearts (67).…”
Section: Pathogenesis Of Cardiac Atrophy In Cancer Cachexia: Protein mentioning
confidence: 96%
See 2 more Smart Citations
“…Autophagy is a highly conserved lysosome‐driven degradation pathway of cellular constituents, normally activated at basal level to maintain cell homeostasis. Emerging data clearly show that induction of autophagy occurs in the skeletal muscle and in the heart in different experimental models of cancer cachexia and that it strongly contributes to the pathogenesis of muscle wasting . Whether autophagy is also modulated in cachectic patient is subject to debate.…”
Section: Introductionmentioning
confidence: 99%